Methionine restriction alleviates age-associated cognitive decline via fibroblast growth factor 21 - Ren, Bo (Redox Biol, 2021)
Methionine restriction (MR) extends lifespan and delays the onset of aging-associated pathologies. However, the effect of MR on age-related cognitive decline remains unclear. Here, we find that a 3-month MR ameliorates working memory, short-term memory, and spatial memory in 15-month-old and 18-month-old mice by preserving synaptic ultrastructure, increasing mitochondrial biogenesis, and reducing the brain MDA level in aged mice hippocampi. Transcriptome data suggest that the receptor of fibroblast growth factor 21 (FGF21)-related gene expressions were altered in the hippocampi of MR-treated aged mice. MR increased FGF21 expression in serum, liver, and brain. Integrative modelling reveals strong correlations among behavioral performance, MR altered nervous structure-related genes, and circulating FGF21 levels. Recombinant FGF21 treatment balanced the cellular redox status, prevented mitochondrial structure damages, and upregulated antioxidant enzymes HO-1 and NQO1 expression by transcriptional activation of Nrf2 in SH-SY5Y cells. Moreover, knockdown of Fgf21 by i.v. injection of adeno-associated virus abolished the neuroprotective effects of MR in aged mice. In conclusion, the MR exhibited the protective effects against age-related behavioral disorders, which could be partly explained by activating circulating FGF21 and promoting mitochondrial biogenesis, and consequently suppressing the neuroinflammation and oxidative damages. These results demonstrate that FGF21 can be used as a potential nutritional factor in dietary restriction-based strategies for improving cognition associated with neurodegeneration disorders.